EDUKASI ENTREPRENEURSHIP MELALUI PROGRAM PKM UNIVERSITAS CIPUTRA PADA SISWA SMA HANG TUAH SURABAYA - SITEPU, RISMAWATI BR; Sembiring, Murpin Josua; Febri, Timotius; Siahaan, Salmon Charles P. T.; Ginting, Adhitya (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2024)
Abstract This service is aimed at students at Hang Tuah High School to develop the spirit, climate, culture, and entrepreneurial activities by educating and encouraging the creation of graduates who are independent and become entrepreneurs through entrepreneurship programs. The subjects of this service are Hang Tuah High School students, in Surabaya. Delivering material about entrepreneurship, being part of the campus which has the tag line Create the word Entrepreneur Ciputra University Surabaya. The outputs of this service include the realization of an effective entrepreneurial development model in developing the spirit, climate, culture, and entrepreneurial activities of students, starting from entrepreneurial education, motivation and demonstrating examples of entrepreneurial activities from the Ciputra University Surabaya campus which are directly handled by Ciputra students who currently on project. The results of this service support the entrepreneurship program that has been established at Hang Tuah 2 Sidoarjo High School. The resulting output is in the form of output and the form of KI for Ciputra University lecturers and students, and was covered in the Malang Posco Media newspaper.